Arab Muslim migrants in Europe between to be save or integrate, a feminist ethnographic study - Fatima Zahra Drim; Sofía Saulesleja (International Journal of Social Communication, 2025)
Our study belongs to the gender ethnographic type, as it is concerned with Muslim women immigrants from North Africa to Europe, as it describes in the form of an ethnographic report their lifestyle there between saved from their society or integration into a different society. The non-probability sample using the participant observation, immersion, coexistence, direct and indirect interview observation tool was specific to the time of the epidemic for a period of three years from November 2018 to December 2021, these women varied in their scientific and practical levels, their intellectual orientations, their ages and their social statuses, which necessitated the reliance on the gender approach and feminist ethnography As a theoretical approach that explains the manifestations of the life of Muslim women between the culture of the country of origin and integration into the future society. Among the results of the study, the gap between the two communities, which reinforces the sexual, racial, and economic inequality that draws the boundaries of affiliation and alienation? Women seek to integrate and assimilate into the new lifestyle while preserving the original culture derived from religion and Arabism, as well as attempting individual, family, and collective advancement. By improving material income and earning financial profit